Acute Transient Oculomotor Nerve Palsy from Presumed Cavernous Angioma in an Infant. (4th July 2018) - Blizzard, Sonya T.; Collins, Megan E.; Miller, Neil R.
ABSTRACT: Cavernous angiomas of the cranial nerves are extremely rare, and those of the oculomotor (third) cranial nerve are rarer still, with no previous cases having been reported in the literature. We report herein the first case of a presumed cavernous angioma involving the subarachnoid portion of the left third nerve presenting as an acute left third nerve palsy in an infant. The child was followed without intervention and the palsy completely resolved. Given the poor functional results with attempted surgical excision and the potential for spontaneous improvement in oculomotor nerve function, it is reasonable to follow patients with these lesions without intervention.